Halal Tourism Settings on Lombok Island - Umami, Allan Mustafa; Alqindy, Fatria Hikmatiar (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Halal tourism arrangements are included in the tourism agenda on Lombok Island. Lombok Island, since the inauguration of international events such as the GP series and super bikes organized by international parties with high reputations, must continue to adjust the provisions regarding halal tourism amidst liberalization in all sectors. The entry of international events is a challenge for the Indonesian government, especially the Lombok region. Lombok, which has a lot of potential for world-class tourist areas and has received world-class awards several times, needs to think about the conditions for halal tourism plans. Halal tourism has different standards, of course the effect of the word halal must be able to prove the quality and quantity of tourism based on halal standards. The formulation of the problem in this research is how is halal tourism regulated on the island of Lombok? The aim of this research is to determine the regulation of halal tourism on the island of Lombok. The research method used in this research is normative legal research methods. The results of this research reveal that the regulation of halal tourism in Lombok is not yet perfect due to the absence of statutory regulations equivalent to laws that specifically regulate halal tourism. Tourism regulations in New Lombok are based on regional government regulations of West Nusa Tenggara province and West Lombok Regency. There are several different definitions between these two rules in regulating halal tourism. Policy regarding the tourism industry in Lombok is still very dependent on the DSN-MUI which does not have a very strong position in making regulations and implementing halal tourism.